Anti-Inflammatory 18β-Glycyrrhetinin Acid Derivatives Produced by Biocatalysis - Fan, Boyi; Jiang, Baocheng; Yan, Sensen; Xu, Bohui; Huang, Huilian; Chen, Guangtong (Planta Medica, 2019)
In this study, the biocatalysis of 18β-glycyrrhetinic acid by two strains of filamentous fungi, namely Rhizopus arrhizus AS 3.2893 and Circinella muscae AS 3.2695, was investigated. Scaled-up biotransformation reactions yielded 14 metabolites. Their structures were established based on extensive nuclear magnetic resonance and high-resolution electrospray ionization mass spectrometry data analyses, and seven of them are new compounds. The two fungal strains exhibited distinct biocatalytic features. R. arrhizus could catalyze hydroxylation and carbonylation reactions, whereas C. muscae preferred to catalyze hydroxylation and glycosidation reactions. These highly specific reactions are difficult to achieve by chemical synthesis, particularly under mild conditions. Furthermore, we found that most of the metabolites exhibited pronounced inhibitory activities on lipopolysaccharides-induced nitric oxide production in RAW264.7 cells. These biotransformed derivatives of 18β-glycyrrhetinic acid could be potential anti-inflammatory agents.
Keywords: Rhizopus arrhizus; Circinella muscae; biotransformation; 18β-glycyrrhetinic acid; anti-inflammatory activity; Glycyrrhiza glabra; Fabaceae